Prognostic signature and therapeutic drug identification for dilated cardiomyopathy based on necroptosis via bioinformatics and experimental validation - Han Yang; Zhenwei Wang; Yawei Xu; Yimei Du; Haibo Yang; Yang Lu (Scientific Reports)
Abstract Necroptosis, a type of programmed cell death, has been increasingly linked to cardiovascular disease development, yet its role in dilated cardiomyopathy (DCM) remains unclear. In this study, we analyzed the GSE5406 dataset from the GEO database to explore necroptosis-related prognostic signatures in DCM using LASSO regression. We identified five necroptosis-related genes (BID, CAMK2B, GLUL, HSP90AB1, CHMP5) that define a necroptosis-related signature with strong predictive value, evidenced by ROC curve areas of 0.852 and 0.957 in training and test sets, respectively. Our analyses, including GO and GSEA enrichment, focused on pathways associated with high necroptosis-related scores (NRS) and revealed significant immune cell infiltration. Notably, nTreg and iTreg cells were enriched in the high NRS group, while CD8 naive T cells and CD8 T cells positively correlated with NRS. Small molecule drugs fenofibrate, procyclidine, and tienilic acid emerged as potential therapeutic agents for high-risk patients, with fenofibrate showing efficacy in inhibiting DCM progression in an inflammatory animal model. These findings underscore the clinical relevance of necroptosis-related genes in assessing DCM progression and prognosis and highlight their potential for targeted therapeutic development.